Chromium-containing small pore mesoporous silicas: synthesis, characterization and catalytic behavior in the liquid phase oxidation of cyclohexane - Shylesh, S.; Samuel, Prinson P.; Singh, A. P. (Applied Catalysis A-General, 2007)
Organic-inorganic hybrid mesoporous silica materials containing chromium and various organo trialkoxysilanes (chloropropyl, vinyl, methyl) were prepared by the co-condensation method, in the presence of cetyl trimethyl ammonium surfactants. The hybrid material, containing chromium, retains one X-ray diffractogram (XRD) peak up to a molar ratio of 1: 1 between tetra ethyl orthosilicate (TEOS) and organosilane in the synthesis gel. Small pore mesoporous chromium-silica samples can be prepared from the large pore hybrid mesoporous chromium samples by calcination. By this method, the pore size of the material can be tailored into the supermicroporous region, without changing the chain length of the surfactant used in the assembly process, as judged from the XRD and N-2 sorption isotherms. The shrinkage in pore size is dependent on the nature and percentage of the organic pendant groups, such that the chloro propyl and vinyl pendant mesoporous material show more pore size shrinkage than the smaller methyl pendant units. Because of the tailorable pore size and with better textural characteristics, the chromium samples show better catalytic activity in the aerial oxidation reaction of cyclohexane than the conventional chromium-containing mesoporous material, like Cr-MCM-41, under a solvent free system. Among the porous chromium catalysts, the samples prepared using chloro propyl silane show higher cyclohexane conversion and cyclohexanone selectivity and behave as a true heterogeneous catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chromium; Cyclohexane; Oxidation; small pore silicas

Bridging the gap between micropores and mesopores by the controlled transformation of bifunctional periodic mesoporous silicas - Shylesh, S.; Srilakshini, Ch.; Singh, A. P.; Anderson, B. G. (Microporous and Mesoporous Materials, 2008)
Novel bifunctional periodic mesoporous silicas having high content of organic groups in the pore channels and chromium in the frame wall has been synthesized by direct co-condensation method, using organo trialkoxysilanes (chloro propyl, vinyl, methyl), chromium nitrate and tetraethyl orthosilicate, in presence of cetyltrimethyl ammonium surfactants. The obtained materials show one main peak in the XRD patterns up to a molar ratio of 1: 1 between TEOS and organosilane in the synthesis gel and N-2 adsorption-desorption analysis shows that the mesopore structure remains intact after the surfactant removal process. Among the organosilanes, chloro propyl and vinyl pendant chromium samples shows a shift in the main peak to higher 2-theta values with a corresponding decrease in pore volume and pore diameter, with the percentage of organosilane functionalization. Small-pore silicas and chromium silicas can be prepared from the large pore mesoporous MCM-41, by effectively removing the organic groups by calcination. By this method, the pore size of the material can be tailored into the super-microporous region, without changing the chain length of the surfactant used in the assembly process. The shrinkage in pore size is dependent on the nature and percentage of the organic pendant groups that the chloro propyl and vinyl pendant mesoporous materials show the maximum pore size shrinkage than the small chain length methyl units. Because of the tailorable pore size and with better textural characteristics, chromium-silica materials find applications in the field of shape selective heterogeneous catalysis, as demonstrated in the oxidation reaction of cyclohexane, than the conventional metal-containing mesoporous materials. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: bifunctional silicas; chromium; Cyclohexane; MCM-41; Oxidation

Selective oxidation of cyclohexane to cyclohexanone using chromium oxide supported mesoporous MCM-41 nanospheres: probing the nature of catalytically active chromium sites - Betsy, Kurisingal J.; Nayak, Chandrani; Lazar, Anish; Krishnan, Athira; Bhattacharyya, Dibyendu; Jha, Shambhu N.; Vinod, Chathakudath P. (ChemCatChem, 2018)
Highly dispersed chromium oxide supported mesoporous MCM-41 nanosphere catalysts have been synthesized using a simple wet impregnation method. This work is devoted to a systematic study to reveal the active Cr sites in chromium oxide supported MCM-41 nanosphere catalysts for the selective oxidation of cyclohexane to cyclohexanone. To probe the nature of the active species, we synthesized 0.5-10wt% Cr loaded catalysts and characterized them by using XRD, UV/Vis spectroscopy, Raman spectroscopy, X-ray photoelectron spectroscopy, extended X-ray absorption fine structure analysis, X-ray absorption near edge structure analysis, N-2 sorption analysis, FTIR spectroscopy, (SiNMR)-Si-29 spectroscopy, SEM, and TEM. The liquid-phase oxidation of cyclohexane to cyclohexanone (99% selectivity) was performed under mild reaction conditions, and the results reveal clearly that the 5wt% Cr loaded catalyst was optimum for the reaction. The initial composition of isolated Cr3+ species in the catalyst is the major factor that influences the enhanced activity for cyclohexane oxidation.
Keywords: chromium; heterogeneous catalysis; Nanostructures; Oxidation; supported catalysts